Análise da micromedição do volume de água potável domiciliar e sua influência no cálculo das perdas no sistema de distribuição - Borges, Elsio Júnior Bonati (2007)
The accelerated degradation of natural hydric resources, along with the increasing demand for drinking water, urge for programs which deal with the losses of this essential good, and that are essential for environmental managers. This work is inserted in this context, with the objective of evaluating the magnitude of the measurement error of the hydrometers installed in Uberlândia-MG, when subjected to consumption variations. There have been comparisons of the equipment commonly used with systems that are more sensible to the measurement of low flows, in order to verify the reliability of the micro-measurement accomplished and serve as subsidy for the calculation of the indicators of losses. The evaluation showed that the equipment with larger sensibility totaled, on average, a volume 13.56% higher than the more commonly used hydrometer.